(untitled) (Journal of the Bangladesh Agricultural University, 2026)
Milk is a vital nutrient source, but in Bangladesh, its quality is often compromised by dilution and adulteration. Regular, systematic monitoring of open-market milk quality is vital for protecting public health. This study compared the physicochemical properties, nutrient composition, and common adulterants in raw milk from local vendors to commercial pasteurized/Ultra-High-Temperature (UHT) treated brands available in Mymensingh City. Twenty-four samples (five local sources and three brands, triplicate each) were analyzed for specific gravity (SG), pH, titratable acidity (TA), alcohol stability, moisture, total solids (TS), solids-not-fat (SNF), ash, fat, protein, and carbohydrate, using standard methods. Qualitative tests for added sugar, formalin, and added urea were also performed. Data were statistically analyzed by one-way ANOVA (P ≤ 0.05) using a Completely Randomized Design followed by Duncan’s Multiple Range Test. Results showed statistically significant (P ≤ 0.05) differences between the samples across all parameters. Branded milk, particularly Brand-1, had higher density and solids content (e.g., specific gravity ≈1.030, total solids ≈13.0%) and correspondingly lower moisture (≈87%) than local samples (SG ≈1.027-1.028; TS ≤ 11.2%). Four of the five open-market samples were heavily diluted: the sample from Churkhai had the highest moisture (≈90.6%) and lowest TS (9.44%), SNF (6.77%), ash (0.03%, indicating severe dilution), fat (2.67%), protein (3.18%), and carbohydrate (3.57%). In contrast, Brand-1 showed the lowest moisture (86.97%), and the highest TS (13.03%) and SNF (9.50%). The alcohol stability test was negative for all samples. Adulterant screening found no formalin or urea in any sample; only a single replicate of the Sutiakhali local sample was positive for added sugar. In conclusion, open-market milk in Mymensingh City was significantly poorer in nutritional composition than commercial milk. The predominant fraud is massive water dilution, not toxic chemicals. These findings underscore the need for stricter regulation and routine quality monitoring in the informal milk market. J Bangladesh Agril Univ 22(4): 38–44, 2024